The influence of thermal field in the electric arc welding of X60 carbon steel components in the CO2 environment. (25th June 2016) - Cîndea, Lenuţa; Haţiegan, Cornel; Pop, Nicolina; Negrea, Romeo; Răduca, Eugen; Gillich, Gilbert-Rainer; Dănuţ, Moşteanu; Nedeloni, Marian-Dumitru
Highlights: Equation which governing the thermal field represents a Gaussian distribution. 3D simulation the electrical arc as a source of mobile welding. Temperature value is highest at 2 s to any position of the heat source. Good correlation between the measured and simulated temperature. Abstract: This paper studies the influence of the thermal field on X60 carbon steel components during welding in CO2 environment given that the heat source (electric arc) moves. Through ANSYS software for modeling and simulation of welded components was considered butt welding of two X60 steel plates. The modeled temperature decrease to a value equal to the ambient temperature at the point infinity and obtain the best possible accuracy were used the Solid 90 type elements (finite element methods) for air and space component and, respectively, the Infinite 111 type elements for infinite space. Following the simulation, it can be represented the temperatures reached by the electric arc on the surface of the molten matrix metal, temperatures above the melting point of the steel, areas where one can see the movement of the molten metal bath along the seam. Simultaneously, it also represented as graphs, spatial variation in temperature after different directions for different durations of time. For experimental measurements, after modeling and simulation of welding processes in the shielding gas (CO2 ) it is absolutely necessary to proceed to confirm the theoretical premises through experimental research in real conditions effective welding. This temperature was measured in three areas located along the seam, covering the evolution of the temperature in a point on the axis of the seam, located at the beginning, middle or end of the seam. Using the simulation method of the time variation for thermal field, one can carry out experiments that give values close to the real ones, facilitating the work of technologies, shortening the compile time for welding technologies on different welted structures.